Elaboración de una propuesta para la implementación de Gobierno de Tecnologías de Información mediante el modelo GTI4U en la Universidad Nacional de Loja - Calderón Sanmartín, Jhon Alexander (2023)
The governance of Information Technology (IT) is a reference framework that allows the integration of information, processes and IT resources with organizational strategies. Higher Education Institutions (HEIs) in Ecuador have not implemented IT governance models, due to the complexity and high costs of their execution. For this reason, this project is aimed at generating initial conditions and capacities for the future implementation of IT governance at the National University of Loja (UNL), the GTI4U model (IT Governance Model for Universities) will be used because it is a reference of the CRUE (CRUE Spanish Universities), the same one that is considered optimal for its implementation in HEIs. It begins with the contextualization of IT governance and the GTI4U model, to continue with the development of the proposal as a framework for its applicability, and concludes with the formulation through an example of the current level of maturity and IT governance objective. , in order to increase the capacity and maturity of organizational processes and their integration of IT with the strategic objectives of the university. For the present titling work, a series of best practices and guidelines proposed by PMBOK were used, based on the detailed definition of the work team, work packages, risk identification and analysis, in order to comply with what was planned in the management and direction of the project. Keywords: IT Government, GTI4U, Information Technologies, Digital Transformation.